2016
DOI: 10.1021/acs.jmedchem.6b00747
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pyrimidine Toll-like Receptor 7 and 8 Dual Agonists to Treat Hepatitis B Virus

Abstract: Toll-like receptor (TLR) 7 and 8 agonists can potentially be used in the treatment of viral infections and are particularly promising for chronic hepatitis B virus (HBV) infection. An internal screening effort identified a pyrimidine Toll-like receptor 7 and 8 dual agonist. This provided a novel alternative over the previously reported adenine and pteridone type of agonists. Structure-activity relationship, lead optimization, in silico docking, pharmacokinetics, and demonstration of ex vivo and in vivo cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 40 publications
0
37
0
Order By: Relevance
“…Using WBP-1 and BALB/c mice, we demonstrated that the antiviral compound R848 (Resiquimod) can be used to effectively treat SARS-CoV-2 infection. As a dual TLR7/TLR8 agonist, R848 is used as a drug to help treat topical viral infections, tumors and asthma, or as an adjuvant to increase the effective of vaccines [48]. The activation of Toll-like receptors triggers a signaling cascade that leads to the production of interferon-stimulated genes and proinflammatory cytokines with antiviral activities.…”
Section: Discussionmentioning
confidence: 99%
“…Using WBP-1 and BALB/c mice, we demonstrated that the antiviral compound R848 (Resiquimod) can be used to effectively treat SARS-CoV-2 infection. As a dual TLR7/TLR8 agonist, R848 is used as a drug to help treat topical viral infections, tumors and asthma, or as an adjuvant to increase the effective of vaccines [48]. The activation of Toll-like receptors triggers a signaling cascade that leads to the production of interferon-stimulated genes and proinflammatory cytokines with antiviral activities.…”
Section: Discussionmentioning
confidence: 99%
“…The same compound also caused no significant HBsAg decline in combination with tenofovir in treatment-naïve patients [ 156 ]. Pyrimidine analogues were recently identified as potent dual TLR7/8 modulators ( Figure 6 ii) [ 157 ]. Structural modifications led to novel 2,4-diaminoquinazoline dual TLR7/8 agonists with increased potency and proved that changing the stereochemistry in one single stereocenter leads to TLR8 selectivity ( Figure 6 iii) [ 158 ].…”
Section: Novel Therapeutic Strategiesmentioning
confidence: 99%
“… Innate immunity modulators; ( i ) Selective TLR7 agonist [ 163 ] ( ii ) TLR7/8 dual agonist [ 157 ] ( iii ) Dual TLR7/8 agonist. (R) isomer results in selective TLR8 agonist [ 158 ] ( iv ) Selective TLR8 agonist [ 159 ].…”
Section: Novel Therapeutic Strategiesmentioning
confidence: 99%
“…Resiquimod (R848), the synthetic dual agonist of hTLR7/8, has been proven effective for genital herpes treatment (Kanzler, Barrat, Hessel, & Coffman, ). Subsequently, a series of imidazo‐quinazolines, thiazolo‐quinolines, furo‐quinolines, and more recent furo‐pyridines and amino‐imidazoles analogues have been discovered as potential hTLR8 agonists (Figure a) (Beesu et al, , ; Kokatla et al, ; McGowan et al, ; Salunke et al, ; Yoo et al, ). The hTLR8 antagonists currently under development are structural analogue of agonists, for example, 3H imidazoquinolines for TLR7/8 dual antagonists(Shukla, Malladi, Day, & David, ), pyrazolo[1,5‐ a ]pyrimidine derivatives and quinoline derivatives as hTLR8 antagonists (Figure b) (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%